2020
DOI: 10.1021/acs.joc.0c01879
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-Catalyzed Electrochemical Synthesis of Indolines through Dehydrogenative [3 + 2] Annulation with H2 Evolution

Abstract: A dehydrogenative [3 + 2] annulation reaction of aniline derivatives and alkenes has been developed via the ruthenium-electron catalytic systems for the synthesis of versatile indolines. Electricity is used as a sustainable oxidant to regenerate the active Ru­(II) catalyst and promote H2 evolution. This protocol is ecofriendly and easy to handle as it uses a simple undivided cell in mild conditions without the employment of metal oxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…product along with the formation of Ru-VII complex, which is re-oxidised anodically (Scheme 69). Shen et al 145 reported the synthesis of indolines (196) via dehydrogenative [3+2] annulation of aniline derivatives with terminal alkene in the presence of Ru(II) metal catalyst. In order to find the most efficient reaction conditions, the initial pre-screening of the reaction was performed using N-2-pyrimidyl-substituted aniline (195b) and styrene (31a) as model substrates.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…product along with the formation of Ru-VII complex, which is re-oxidised anodically (Scheme 69). Shen et al 145 reported the synthesis of indolines (196) via dehydrogenative [3+2] annulation of aniline derivatives with terminal alkene in the presence of Ru(II) metal catalyst. In order to find the most efficient reaction conditions, the initial pre-screening of the reaction was performed using N-2-pyrimidyl-substituted aniline (195b) and styrene (31a) as model substrates.…”
Section: Organic and Biomolecular Chemistry Reviewmentioning
confidence: 99%
“…Increasing or decreasing the amount of Li 2 CO 3 also reduced the yield (entries [11][12]. Control experiments verified the crucial role of Li 2 CO 3 , rhodium catalysts and electricity (entries [13][14][15]. Three other typical transition metals were also explored, but no target products were obtained (entries [16][17][18].…”
Section: Resultsmentioning
confidence: 97%
“…A catalytic cycle is proposed based on the experimental results obtained and previous reports (Scheme ). ,,, The active catalyst C is generated from [Cp*RhCl 2 ] 2 in the presence of AgSbF 6 , Ag 2 CO 3 , and 1a through the directed ortho-rhodation . The coordination of an alkene to the rhodium complex C forms complex E′ , which undergoes the migratory insertion of an alkene into a Rh–C bond to generates the eight-membered Rh complex E .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the use of a metal-catalyzed C–H activation/alkene cyclization cascade to construct indoline frameworks has been less explored because the intermediate A is prone to undergo β-hydride elimination, which then leads to the formation of alkenylated products (Scheme a) . To overcome these limitations, various strategies have been developed to retard the β-hydride elimination and various C–H activation/alkene cyclization reactions, leading to the production of indoline derivatives. However, all of the examples reported thus far exclusively lead to the production of C2-substituted indolines, and only activated alkenes, such as 1,3-dienes, norbornene, vinylnaphthalene, acrylic esters, styrenes, ,, and allyl acetates can be used as an alkene partner. To the best of our knowledge, there are no reported examples of the selective production of C3-substituted indolines via C–H activation/alkene cyclization (Scheme b). …”
Section: Introductionmentioning
confidence: 99%